Introduction and validation of a surgical ward round checklist to improve surgical ward round performance in a tertiary vascular service. Issue 7 (1st May 2020) - Tranter‐Entwistle, Isaac; Best, Katherine; Ianev, Ross; Beresford, Timothy; McCombie, Andrew; Laws, Peter
Abstract: Background: Surgeons administer care in an increasingly complex clinical environment. Time constraints put strain on individual clinicians and the multidisciplinary team, increasing the risk of human errors. The World Health Organization surgical checklist has shown to mitigate this risk perioperatively. We describe the development, introduction and outcomes of a novel ward round safety checklist. Methods: The vascular team ward rounds at Christchurch Hospital were assessed over a 2‐week period for ward round quality indicators. A ward round safety checklist was developed and then introduced. Two further assessments were conducted to evaluate for improvement in the ward round quality indicators. Ward rounds were timed with the length of each consultation recorded and staff perception assessed. Results: Significant gains across both clinical indicators and staff feedback measures were observed. Of the 21 ward round quality indicators, 20 showed statistically significant improvement, as did all subjective measures. Significant improvements included observation chart review (20% to 75% to 81%), drug chart review (10% to 54% to 78.6%) and anticoagulation/antiplatelet treatment (32% to 61% to 58.1%) ( P < 0.05). Mean consultation time per patient did not increase (3 min 58 s to 3 min 48 s and 4 min 30 s) ( P = 0.857 and P = 0.119). Conclusion: This study provides evidence that introducing a structured ward round safety checklist improved ward round quality, without adversely affecting consultation time. The familiar checklist structure promotes its acceptance and team cohesion. Whether the improvements observed translate to improved patient outcomes and reduced adverse events reporting is the subject of ongoing study. Abstract : Ward rounds are administered in an increasingly complex clinical environment. The introduction of a ward round safety checklist significantly improved ward round performance without increasing ward round length.